Formative evaluation in the framework of the competences approach (Revista Innova Educación, 2019)
The objective of the article was to carry out a bibliographic review on the formative evaluation, given the problems observed in basic education, referring to the difficulties in the evaluation practice in the classroom, from the management of the concepts, the planning and the application of the same in the development of the teaching-learning process, this in the competences-centered approach to learning; answering the questions; what and how we understand formative evaluation, what is evaluated, what is evaluated, what is evaluated, when is evaluated, who evaluates and how it is evaluated. The methodology used was focused on qualitative documentary research. It is concluded that the individual and collective performance of the students who are coparticipants of their evaluation must be evaluated, this implies the feedback according to the evidences, thus generating a transformation of the evaluative practice in the improvement of the learning with autonomy and reflection.
Keywords: Formative evaluation; competences; evaluative practices; learning; teaching